A Study of Environmental Factors in Low Vision Rehabilitation - Øien, Turid Borgestrand (Frontiers in Rehabilitation Sciences, 2022)
Healthcare has the past decades shifted from a narrow medical perspective to a more holistic, biopsychosocial perspective. Disability understood as a contextual condition constituted by the relation of the individual to their social and physical context. The disability model of the International Classification of Functions (ICF) contextualizes activity, participation, body functions and structure by including environmental and personal factors. However, illustrated by the consideration of the environmental factors as a neutral dimension, the dynamic interrelation of the individual parts of the system is rather unchartered. In 2017–2019, a lighting assessment was developed and tested on 60 participants in low vision rehabilitation. An action research project accompanied the pilot study from 2018. Ethnographic participatory observations of the low vision consultants in 15 consultations, semi-structured interviews, and a document analysis of the project material of the pilot project has been analyzed using the theoretical framework of science and technology studies. Mapping the physical environment showed a range of factors from spatial organization to luminaires and light bulbs. Moreover, in relation to specific activities, relevant factors were identified and assessed, and in the intervention adjusted to relevant personal and social factors. Identifying overlapping personal, environmental, and professional spheres illustrates the complexity of practicing rehabilitation in people’s everyday lives. Acknowledging and coordinating different versions of lighting enabled low vision consultants to work across these spheres relationally. ICF was embedded in the practice of low vision consultants as a frame of reference, however, implementing this framework occurred through an assemblage of tools from different fields. The focus on lighting as an active element in low vision rehabilitation demonstrated a way to work across the personal and environmental to reduce the gap that caused disability. In everyday life, the physical environment was pivotal in the person–environment relationship and in enabling or disabling the individual. However, the physical environment was also key to the rehabilitation process, facilitating the individual’s learning and change processes and reconfiguring their understanding and use of the environment. Consequently, the physical environment was not a neutral background to the other factors but rather enabling the rehabilitation and recovery processes.